Impact of Overhydration on Left Ventricular Hypertrophy in Patients With Chronic Kidney Disease - Sun, Lianqin; Li, Qing; Sun, Zhiying; Duan, Suyan; Nie, Guangyan; Dong, Jiaxin; Zhang, Chengning; Zeng, Ming; Sun, Bin; Yuan, Yanggang; Wang, Ningning; Mao, Huijuan; et al. (Frontiers in Nutrition, 2022)
Objectives Volume overload is a frequent feature related to left ventricular hypertrophy (LVH) in dialysis patients, but its influence on chronic kidney disease (CKD) patients not on dialysis has not been accurately uncovered. This paper was to examine the relationship between overhydration (OH) and LVH in CKD patients not yet on dialysis. Methods A total of 302 patients with CKD stages 1 to 4 were included. Participants were divided into different subgroups according to occurring LVH or not, and OH tertiles. Clinical and laboratory parameters were compared among groups. Spearman correlation analyses were adopted to explore the relationships of echocardiographic findings with clinical and laboratory characteristics. Binary Logistic regression models were performed to estimate the odds ratios for the associations between OH and LVH. Restricted cubic splines were implemented to assess possible nonlinear relationship between OH and LVH. LVH was defined as left ventricular mass index (LVMI) ˃ 115 g/m2 in men and ˃ 95 g/m2 in women. Results Of enrolled patients with CKD, mean age was 45.03±15.14 years old, 165(54.6%) cases were male, and 65(21.5%) cases had LVH. Spearman correlation analyses revealed that OH was positively correlated with LVMI (r = 0.263, P ˂ 0.001). After adjustment for age, gender, BMI, SBP, eGFR, urinary sodium excretion, and urinary protein excretion, multivariate Logistic regression analyses demonstrated that both the middle and highest tertile of OH was associated with increased odds of LVH (OR: 3.336 [1.300-8.566], P = 0.012; OR: 5.697 [1.959-16.567], P = 0.001, respectively), in comparison to the lowest tierce. Restricted cubic spline analyses were employed to investigate the relationship between OH and LVH, which unfolded a significant nonlinear association (P for nonlinear = 0.0068). Conclusions These findings suggest that higher level of OH was associated with a higher occurrence of LVH in CKD patients not on dialysis. Keywords overhydration, left ventricular mass index, left ventricular hypertrophy, chronic kidney disease